Central and Peripheral Effects of Urotensin II and Urotensin II-Related Peptides on Cardiac Baroreflex Sensitivity in Trout - Lancien, Frédéric; Vanegas, Gilmer; Leprince, Jérôme; Vaudry, Hubert; Le Mével, Jean-Claude (Frontiers in Neuroscience, 2017)
The baroreflex response is an essential component of the cardiovascular regulation that buffers abrupt changes in blood pressure to maintain homeostasis. Urotensin II (UII) and its receptor UT are present in the brain and in peripheral cardiovascular tissues of fish and mammals. Intracerebroventricular (ICV) injection of UII in these vertebrates provokes hypertension and tachycardia, suggesting that the cardio-inhibitory baroreflex response is impaired. Since nothing is known about the effect of UII on the cardiac baroreflex sensitivity (BRS), we decided to clarify the changes in spontaneous BRS using a cross spectral analysis technique of systolic blood pressure (SBP) and R-R interval variabilities after ICV and intra-arterial (IA) injections of trout UII in the unanesthetized trout. We contrasted the effects of UII with those observed for the UII-related peptides (URP), URP1 and URP2. Compared with vehicle-injected trout, ICV injection of UII (5-500 pmol) produced a gradual increase in SBP, a decrease in the R-R interval (reflecting a tachycardia) associated with a dose-dependent reduction of the BRS. The threshold dose for a significant effect on these parameters was 50 pmol (BRS; - 55%; 1450 ± 165 msec/kPa vs 3240 ± 300 msec/kPa; P<0.05). Only the 500-pmol dose of URP2 caused a significant increase in SBP without changing significantly the R-R interval but reduced the BRS. IA injection of UII (5-500 pmol) caused a dose-dependent elevation of SBP. Contrasting with the ICV effects of UII, the R-R interval increased (reflecting a bradycardia) up to the 50-pmol dose while the BRS remained unchanged (50 pmol; 2530 ± 270 msec/kPa vs 2600 ± 180 msec/kPa; P<0.05). Nonetheless, the highest dose of UII reduced the BRS as did the highest dose of URP1. In conclusion, the contrasting effect of low picomolar doses of UII after central and peripheral injection on the BRS suggests that only the central urotensinergic system is involved in the attenuation of the BRS. The limited effects of URP1 and URP2 on the BRS, indicate that the action of UII is specific for this peptide. Further studies are required to elucidate the site(s) and mechanisms of action of UII on the BRS.